Interaction of social support and depressive symptoms on antiretroviral therapy adherence among people living with HIV in South Africa - Muziwandile Q. Luthuli; Johannes John-Langba (AOSIS, 2024)
Background: Depression consistently emerges as a significant predictor of poor antiretroviral therapy (ART) adherence among adult people living with human immunodeficiency virus (PLHIV). However, a gap exists regarding how social support and depressive symptoms can interact to influence ART adherence among adult PLHIV in South Africa (SA). Aim: To investigate the interaction between social support and depressive symptoms on ART adherence among adult PLHIV. Setting: A tertiary hospital in Durban, KwaZulu-Natal province of SA. Methods: Utilising a quantitative cross-sectional research design along with time location sampling technique (TLS); the study recruited 201 adult patients enrolled in an ART programme. Results: The results indicated that depressive symptoms were significantly associated with ART adherence with and without the interaction (B = -0.105; odds ratios [OR] 0.901; 95% confidence intervals [CI] = 0.827, 0.981; p = 0.016), while social support was not significantly associated with ART adherence (B = 0.007; OR 1.007; 95%CI = 0.989, 1.025; p = 0.475). However, a statistically significant interaction was found between social support and depressive symptoms (B = -0.006; OR 0.994; 95%CI = 0.989, 1.000; p = 0.037) on ART adherence. Conclusion: Based on the results, depressive symptoms significantly influenced ART adherence. However, social support did not buffer the adverse effects of clinical depression associated with poor ART adherence. Contribution: This study provides an evidence-based approach to address gaps in the mental health and social well-being of PLHIV in the context of ART adherence.